The Centered athlete : a conditioning program for your mind - Hendricks, Ga; Carlson, Jon (Englewood Cliffs, New Jersey : Prentice-Hall, 1982)
Athletics are for fun, fitness, and feeling better about ourselves: they can help us relax, enjoy companionship, and find civilized outlets for aggressive impulses.
1. Centering, Sports, and The Game of Life -- 2. In the mind's eye: Imagery Experience for Centered Athletes -- 3. Body Expansion: Stretching Exercises for all Sports -- 4. Experiments in Centered Running -- 5. The Shield: A New Approach to Centered Tennis -- 6. The Centered Racqueteer: Lessons in Centered Tennis -- 7. Centering on the Mountains: Experiments in Centered Skiing -- 8. A Mental Conditioning Program for Athletes -- 9. The Centered Walker.
Includes index.
Keywords: SPORTS -- PSYCHOLOGICAL ASPECTS